Use of Both Serum Cystatin C and Creatinine as Diagnostic Criteria for Contrast‐Induced Acute Kidney Injury and Its Clinical Implications - Wei‐feng Zhang; Tuo Zhang; Ding Ding; Shi‐qun Sun; Xiao‐lei Wang; Shi‐chun Chu; Ling‐hong Shen; Ben He (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundContrast‐induced acute kidney injury (CI‐AKI) was traditionally defined as an increase in serum creatinine (sCr) after contrast media exposure. Recently, serum cystatin C (sCyC) has been proposed as an alternative to detect acute changes in renal function. The clinical implications of combining sCyC and sCr to diagnose CI‐AKI remain unknown. Methods and ResultsOne thousand seventy‐one consecutive patients undergoing coronary angiography/intervention were prospectively enrolled. SCyC and sCr were assessed at baseline and 24 to 48 hours after contrast media exposure. CI‐AKI determined by sCr (CI‐AKIsCr) was defined as an sCr increase greater than 0.3 mg/dL or 50% from baseline. Major adverse events at 12 months were assessed. CI‐AKIsCr developed in 25 patients (2.3%). Twelve‐month follow‐up was available for 1063 patients; major adverse events occurred in 61 patients (5.7%). By receiver operating characteristic curve analysis, an sCyC increase of greater than 15% was the optimal cutoff for CI‐AKIsCr detection, which occurred in 187 patients (17.4%). To evaluate the use of both sCyC and sCr as CI‐AKI diagnostic criteria, we stratified patients into 3 groups: no CI‐AKI, CI‐AKI detected by a single marker, and CI‐AKI detected by both markers. Multivariable logistic regression revealed that the predictability of major adverse events increased in a stepwise fashion in the 3 groups (no‐CI‐AKI group as the reference, CI‐AKI detected by a single marker: odds ratio=2.25, 95% CI: 1.24–4.10, P<0.01; CI‐AKI detected by both markers: odds ratio=10.00, 95% CI: 3.13–31.91, P<0.001). ConclusionsCombining sCyC and sCr to diagnose CI‐AKI would be beneficial for risk stratification and prognosis in patients after contrast media exposure.